Development and validation of a Chinese general practitioners’ ability to recognise and manage depression assessment scale: a cross-sectional study - Xuemei Sun; Wen Zhong; Yuqin Zhang; Dingkui Sun; Yingyan Gao; Xiyang Chen; Weiru Zhang (BMJ Open)
Objectives There is a shortage of reliable tools to evaluate general practitioners’ (GPs) ability to recognise and manage depression. The main aim of this study was to develop and validate a reliable tool for assessing the GPs’ ability to recognise and manage depression.Design A cross-sectional survey incorporating the GPs’ ability to recognise and manage the depression assessment scale, the work was administered between July 2023 and June 2024. GPs’ ability to recognise and manage the depression assessment scale was developed in four phases: (1) item pool construction, (2) expert consultation, (3) exploratory factor analysis for further item reduction and to identify the factor structure of the revised scale and (4) confirmatory factor analyses to confirm the factors identified within the exploratory factor analysis.Setting Primary healthcare in China.Participants A total of 421 GPs participated in the study across phases 3 and 4. Phase 3 included 172 GPs, and phase 4 involved 249 GPs. They had been working in primary healthcare, with 44.42% having more than 10 years of experience. Of the participants, 57% were female.Results The GPs’ ability to recognise and manage the depression assessment scale comprised two dimensions, with 24 items. Two factors explained 66.62% of the items’ variance through exploratory factor analysis. Confirmatory factor analysis confirmed two dimensions of the scale and produced appropriate Goodness of Fit Indexes. Reliability was robust, with composite reliability coefficients exceeding 0.60, Cronbach’s alpha at 0.96 and a Spearman-Brown coefficient of 0.86.Conclusions The newly developed scale is a reliable and valid tool for assessing GPs’ abilities to recognise and manage depression. It is suitable for large-scale surveys, particularly in underdeveloped regions, and can help identify gaps in knowledge. The scale results highlight areas where GPs’ skills are lacking, enabling the design of targeted continuing education programmes. It can also assess the effectiveness of depression training courses, providing a foundation for tailored interventions.